Syrians' acceptance of digital lectures: a case study. (2nd January 2016) - Ramadan, Reem
Abstract: Technology-based learning modules are mostly challenged by their acceptance. A single-case study and mixed research method are used to explore a unique situation of applying digital lectures at the postgraduate Programmes at the Faculty of Tourism at Damascus University as a solution for brain drain in the Syrian higher education system. Results indicate that Performance Expectancy, Effort Expectancy (EE), Personal Innovativeness and Satisfaction with the Quality of Services have a significant effect on students' Behavioural Intention to accept digital lectures. This effect was stronger for males. However, EE was a better predictor for students under 30. In addition, students regarded the use of digital lectures as an alternative plan to continuing their postgraduate studies abroad within the current restrictions on Syrians. For the future successful implementation of e-learning modules, infrastructure-related issues should be taken into account. The study recommends universities going through brain drain and similar crisis situations to utilise digital lectures.